Pengaruh LKS Berbasis Problem Solving untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa - Putri, Lisa Rahma; Rudibyani, Ratu Beta; Sofya, Emmawaty (Jurnal Pendidikan MIPA, 2018)
The Effect of Problem Solving Based Worksheet to Improve Creative Thinking Skills Students. This research aims to describe the effect of using problem solving based worksheet to improve students creative thinking skills in electrolyte and non-electrolyte solution topic. This research uses quasi experiment method with Non-Equivalent Pretest Posttest Control Group Design. The population in this research was class X Senior high school N 13 Bandarlampung. The sampel used was cluster random sampling, the class X MIPA 1 was the experimental class and X MIPA 5 was the control class. To prove the students worksheet based on problem solving is influential in improving students creative thinking skills, then a measure of influence effect size. The result of data analysis showed that students creative thinking skills had a large influence on the experimental class compared to the control class. Based on the results of the research it can be concluded that problem solving based worksheet has large influence in improving students creative thinking skills in electrolyte and non-electrolyte solution topic.Keywords: problem solving based student worksheet, creative thinking skills, electrolyte and non-elektrolyte solution DOI: http://dx.doi.org/10.23960/jpmipa/v19i1.pp25-36